DINAMIKA PERGULATAN POLITIK DAN PEMIKIRAN FORMALISASI SYARIAH PADA ERA REFORMASI - Zudi Setiawan (SPEKTRUM, 2008)
AbstractThe research shows that Reformation era has brought a great transformation in the development of politics in Indonesia. The transition a long with political freedom has given anychance for the emergence of Islamic movement like Hizbut Tahrir Indonesia (HTI), Majelis Mujahidin Indonesia (MMI), Front Pembela Islam ( FPI), Laskar Jihad, etc. This emergenceinquires some petitions, and one of them is the implementation of Shariah as a positive law in Indonesia. Even, HTI has broader petition i.e. the realization of Khilafah Islamiyah that makes the world united in the frame of Khilafah State. Moreover, Reformation era has given chance forthe establishment of Islamic Parties. In this Reformation era, PPP stands up for the implementation of Jakarta Charter in the constitution but it always faces obstacles. Oppositewith PKS that doesn’t mention if their program relates with the implementation of Shariah as a positive law in Indonesia. Therefore, PPP and PKS still put it base in Pancasila and maintain Unitary State Republic of Indonesia as the final form of national system.Key Words : : the implementation of Shariah, Khilafah Islamiyah, Islamic movement